2019
DOI: 10.1155/2019/9850302
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Experimental Study of Focused Wave Action on a Partially Immersed Box

Abstract: Focused wave is a practical laboratory method for reproducing extreme waves that cause catastrophic damage to marine and coastal structures. This paper presents a simple and efficient analytical method for predicting the hydrodynamic pressure and wave forces acting on a partially immersed box when subjected to a focused wave group attack. The boundary value issue of the physical problem is first investigated to derive an analytical formula based on potential flow theory and the matching eigenfunction method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…An indirect confirmation of these conclusions is the results of Losada et al (1992) on the impact of waves on thin impenetrable barriers, where, in particular, it is shown that the horizontal component of the force on a partially immersed barrier increases with increasing submergence. Analytical calculations (Fang and Guo, 2019) of the wave force acting on a partially immersed box when subjected to a focused wave group attack showed that the horizontal wave force increases with the increase of submergence, if this force is written in the dimensionless form of this study, ℎ 2 0 .…”
Section: Dependence Of the Wave Force On The Problem Parametersmentioning
confidence: 83%
“…An indirect confirmation of these conclusions is the results of Losada et al (1992) on the impact of waves on thin impenetrable barriers, where, in particular, it is shown that the horizontal component of the force on a partially immersed barrier increases with increasing submergence. Analytical calculations (Fang and Guo, 2019) of the wave force acting on a partially immersed box when subjected to a focused wave group attack showed that the horizontal wave force increases with the increase of submergence, if this force is written in the dimensionless form of this study, ℎ 2 0 .…”
Section: Dependence Of the Wave Force On The Problem Parametersmentioning
confidence: 83%
“…The Marine environment is complex. There are three main methods to study ocean engineering: theoretical research [4][5][6], numerical simulation [7][8][9], indoor modal and on-site test [10][11][12][13]. Compared with other methods, field monitoring can obtain the raw data of Marine structures and track the effective information in real-time, which provides essential support for offshore installations and reduce the risk of accidents [14,15].…”
Section: Introductionmentioning
confidence: 99%